2004
DOI: 10.4049/jimmunol.172.10.6107
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Phenotype of Virus-Specific T Cell Populations Is Determined by Repetitive Antigenic Stimulation and Environmental Cytokines

Abstract: Based on the expression of the TNFR SFP CD27, two Ag-primed CD8+ T cell subsets can be discerned in the circulation of healthy individuals: CD27+ T cells that produce a variety of cytokines but do not display immediate cytolytic activity; and cytotoxic CD27− T cells, which secrete only IFN-γ and TNF-α. The mechanism that controls the generation of these different phenotypes is unknown. We show that CMV reactivation not only increases the number of virus-specific T cells but also induces their transition from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 55 publications
6
94
0
Order By: Relevance
“…How could this affect our results? It has been described before that immunosuppressed individuals have higher percentages of CMV-specific cells and that these cells have a more differentiated phenotype (9,18,23). We believe that this can be explained by more frequent reactivations of CMV because of insufficient control by the immune system during the latency stage.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…How could this affect our results? It has been described before that immunosuppressed individuals have higher percentages of CMV-specific cells and that these cells have a more differentiated phenotype (9,18,23). We believe that this can be explained by more frequent reactivations of CMV because of insufficient control by the immune system during the latency stage.…”
Section: Discussionmentioning
confidence: 74%
“…Fourth, we observed no changes in CD8 ϩ T cells recognizing other viruses upon primary CMV-infection or in CMV-seropositive individuals during the first year after transplantation. Lastly, it has been shown before that the higher the percentage of CMV-specific CD8 ϩ T cells, the more these cells have a CD27 Ϫ phenotype (23).…”
Section: Discussionmentioning
confidence: 99%
“…CD27 expression is down modulated after repetitive interactions with its ligand, CD70. Down modulation of CD27 of in vitro activated human CD27 + CMV-specific T cells could be blocked with anti-CD70 antibodies [27]. In CD70 transgenic mice in which all B cells express CD70, all mature peripheral T cells lack CD27 expression, whereas thymic T cells, which hardly encounter high CD70 expression, still do express CD27 [46].…”
Section: Discussionmentioning
confidence: 99%
“…CD27-deficient mice show reduced numbers of effector and memory T cells upon influenza infection [21] whereas CD70-transgenic mice showed enhanced numbers and functionally improved effector T cells after influenza or tumor challenge [20]. In vitro studies with human CMVspecific T cells showed that the antigen dose positively correlated with the CD70 expression levels that are induced [27]. Roman et al [50] showed that after influenza infection a broad spectrum of antigen-specific effector and memory CD4 + T cells emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation